Evaporation Loss During Sprinkler Irrigation - F. S. Zazueta (EDIS, 2018)
This study investigates the factors influencing evaporation loss from sprinkler systems during operation. Through analysis, it is determined that evaporation is influenced by climate demand, time of operation, and water droplet surface area. A nomograph is introduced to estimate evaporation loss, with findings suggesting an average daily loss of 1.5 percent in Gainesville, Florida. Moreover, operation during early afternoon hours in typical summer conditions may lead to a 3 percent loss. Conversely, minimal loss is expected during nighttime and early morning operations. Strategies to mitigate evaporation loss include adjusting operating conditions to increase droplet size and avoiding high climate demand periods. Conversely, factors such as using small nozzles and operating at high pressures can exacerbate evaporation loss, particularly during peak climate demand periods. It is emphasized that adherence to manufacturer-recommended pressure ranges is crucial to prevent performance issues.